Postharvest conservation of ‘avalanche’ cut roses with hydroxypropyl methylcellulose-beeswax natural coating - Junior, José Sidnaldo Pinsetta [UNESP]; Mattiuz, Claudia Fabrino Machado; Pereira, Emmanuel Moreira [UNESP]; Mattiuz, Ben-Hur [UNESP] (FapUNIFESP (SciELO), 2019)
The use of postharvest coatings of fruits and vegetables has been the subject of many studies for their ability to extend the shelf life of vegetables. However, little is known about the effect of coatings on postharvest of cut flowers. We evaluated the effect of different concentrations of natural coating based on hydroxypropyl methylcellulose (HPMC) and beeswax (CA) on postharvest of cut roses. White rose cultivar ‘Avalanche’ obtained from commercial production at the bud stage were used. The coating was prepared by the combination of the hydrophilic phase (HPMC) and the lipid phase (CA) suspended in water, resulting in 50g lipids / 100g emulsion. The emulsion was sprayed on the flowers in different volumes: 0 (distilled water); 1.5; 3.0 and 4.5 mL rose-1. The roses were maintained at 20 ± 1 °C and RH> 70% for 9 days for physiological analysis and 12 days for vase life. Data were collected every 3 days for accumulated of fresh mass, water absorption, relative water content (RWC), membrane stability index (MSI) and vase life. The application of 3.0 mL/rose of the coating resulted in higher RWC and MSI throughout the storage time. We conclude that the use of a natural coating of HPMC/beeswax sprayed at 3.0 mL / rose increased the vase life of the ‘Avalanche’ rose by 2 days.
Conservação pós-colheita de rosas de corte ‘avalanche’ com recobrimento natural a base de hidroxipropil metilcelulose e cera de abelha
Keywords: HPMC; Life; Rosa sp.; Vase